Bio-security in small scale poultry farms against avian influenza: knowledge, attitude and practices (Asian Journal of Medical and Biological Research, 2016)
Avian influenza (AI) is considered as one of the greatest global threat for the poultry industry that the animal health sector has ever had to face. It is primarily an infectious disease of birds caused by influenza virus Type A strain. The major concern now is that a highly pathogenic strain (H5N1) has also been shown to transmit to humans and has the potential to be fatal. Since March 2007, outbreaks of highly pathogenic avian influenza (HPAI) have been occurring in commercial and backyard poultry in Bangladesh. Good bio-security practices can help reducing the risk of spreading and controlling the disease. This investigation describes the bio-security practices of small scale poultry holders (500-2000 birds/ farm) of Gazipur district, their knowledge and attitude in prevention and control of avian influenza. This was assessed using prescribed questionnaire. This study has been conducted on 100 poultry raising farmers through household-based individual interviews. Though respondents had different opinions on the magnitude of AI in their respective area, almost everyone realized AI is a big problem for Bangladesh. Generally, the respondents were not aware of the common infection sources such as, sick poultry, their pens, cages, backyard poultry, wild animals, migratory birds etc. Most of the interviewed small scale farmers in this area were not aware about the strict bio-security process like segregation of diseased birds, cleaning and disinfection of premises to prevent AI. Although there was a basic knowledge about the dangers and economic consequences of AI, there needs to be an updating of information on sources of infection, symptoms and prevention techniques, as well as an understanding of the cross species dangers of the infection. The study has, to a large extent, successfully drawn up a picture of how Bangladeshi small holder farmers have perceived and responded to AI and what they have understood and what practices they are taking against AI in their respective areas.Asian J. Med. Biol. Res. December 2015, 1(3): 670-676